Дослідження професійно важливих якостей у водіїв залізничного транспорту - Думський, В.П.; Петровська, Л.О.; Хома, Л.А.; Саджениця, Л.Я. (Актуальні проблеми транспортної медицини, 2007)
В работе акцентируется внимание на то, что в условиях дальнейшей интенсификации железнодорожного транспорта надежности человеческого фактора уделяется все больше внимания. Опыт профессионального отбора, проводимого в лаборатории психофизиологии и гигиены труда СЕС на Львовской железной дороге, и результаты психофизиологических тестирований профессионально важных качеств позволяют с достаточной вероятностью прогнозировать успешность и надежность работы локомотивных бригад, а также эффективность и целесообразность обучения. The attention in the work is concentrated on the fact, that under conditions of further intensification of railway transport the reliability of the human element becomes the factor of growing importance and is more and more attended. The experience of the profesional selektion, that (which) is held in the Laboratory of labour psychophysiology and hygiene at the Sanitary Epidemiological Station of Lviv Railway, and physiological examinations demonstrates, that the vocational choice for the key professions on railway transport determines with a great extent of probability the successfulness and reliability of locomotive crews.